Biomechanical comparison of the double-push technique and the conventional skate skiing technique in cross-country sprint skiing - Stöggl, T.; Müller, E.; Lindinger, S. (Journal of Sports Sciences, 2008)
The aims of the study were to: (1) adapt the "double-push" technique from inline skating to cross-country skiing; (2) compare this new skiing technique with the conventional skate skiing cross-country technique; and (3) test the hypothesis that the double-push technique improves skiing speed in a short sprint. 13 elite skiers performed maximum-speed sprints over 100 m using the double-push skate skiing technique and using the conventional "V2" skate skiing technique. Pole and plantar forces, knee angle, cycle characteristics, and electromyography of nine lower body muscles were analysed. We found that the double-push technique could be successfully transferred to cross-country skiing, and that this new technique is faster than the conventional skate skiing technique. The double-push technique was 2.9 ± 2.2% faster (P < 0.001), which corresponds to a time advantage of 0.41 ± 0.31 s over 100 m. The double-push technique had a longer cycle length and a lower cycle rate, and it was characterized by higher muscle activity, higher knee extension amplitudes and velocities, and higher peak foot forces, especially in the first phase of the push-off. Also, the foot was more loaded laterally in the double-push technique than in the conventional skate skiing technique.